A Model of an Integrated Research and Education Program in Space Weather at a Community College. Issue 1 (4th January 2020) - Damas, M. C.; Ngwira, C. M.; Cheung, T. D.; Marchese, P.; Kuznetsova, M.; Zheng, Y.; Chulaki, A.; Mohamed, A.
Abstract: Community Colleges provide a great opportunity to diversify the space sciences or other science, technology, engineering, and math (STEM) fields due to their large population of underrepresented students. However, since the primary mission of community colleges is teaching, there is a challenge to support undergraduate research training and promote undergraduate research opportunities. Undergraduate research experiences are one of the leading high‐impact practices (HIPs) to encourage students to pursue STEM majors, graduate degrees, and careers. Space weather provides the opportunity to engage undergraduate students in real‐world research due to the accessibility of space mission data sets within open access data repositories. Space weather's impact on Earth's geospace environment, life, and society also provides a compelling real‐world hook to engage students in activities that have a number of impacts including (1) long‐term integration of space weather into the undergraduate curricula; (2) experience in analyzing large geospace data sets, which increases students' computational, critical thinking, and analytical skills, useful for any career; and (3) increase in students' interest in and motivation to study STEM, as well as preparing them for choosing a career path in space science and related fields. The model presented below has the potential to increase the retention, graduation, and transfer rate of community college students to four‐year STEM programs, as well as increase representation and inclusion in space sciences and other related STEM fields. Key Points: Community colleges are important in the STEM pathway for underrepresented minorities and nontraditional students interested in STEM Engaging community college students early in space weather research and activities increase their interest in space science and STEM Using large geospace data sets in the classroom increase students' computational, critical thinking, and data analytical skills